2021
DOI: 10.3389/fimmu.2021.758588
|View full text |Cite
|
Sign up to set email alerts
|

Siglecs Modulate Activities of Immune Cells Through Positive and Negative Regulation of ROS Generation

Abstract: Reactive oxygen species (ROS) are a group of oxygen-containing highly-reactive molecules produced from oxidative metabolic processes or in response to intracellular signals like cytokines and external stimuli like pathogen attack. They regulate a range of physiological processes and are involved in innate immune responses against infectious agents. Deregulation of ROS contributes to a plethora of disease conditions. Sialic acids are carbohydrates, present on cell surfaces or soluble proteins. Sialic acid-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“… 18 Low doses of ROS have positive biological effects in maintaining metabolism, signal transduction, cell proliferation, apoptosis, and the aging process. 19 In contrast, excess ROS can have devastating effects on cells, damaging proteins, lipids, and nucleic acids, causing apoptosis and necrosis in more severe cases. 20 Normally, cells can scavenge ROS, such as Nrf2, which is the most important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Low doses of ROS have positive biological effects in maintaining metabolism, signal transduction, cell proliferation, apoptosis, and the aging process. 19 In contrast, excess ROS can have devastating effects on cells, damaging proteins, lipids, and nucleic acids, causing apoptosis and necrosis in more severe cases. 20 Normally, cells can scavenge ROS, such as Nrf2, which is the most important.…”
Section: Discussionmentioning
confidence: 99%
“…They include superoxide anions (˙O 2− ), hydrogen peroxide (H 2 O 2 ), hydroxyl radicals (˙OH), singlet oxygen (1O 2 ), peroxy radicals (LOO˙), hydrogen peroxide lipids (LOOH), and peroxynitrite (ONOO − ) among others 18 . Low doses of ROS have positive biological effects in maintaining metabolism, signal transduction, cell proliferation, apoptosis, and the aging process 19 . In contrast, excess ROS can have devastating effects on cells, damaging proteins, lipids, and nucleic acids, causing apoptosis and necrosis in more severe cases 20 .…”
Section: Discussionmentioning
confidence: 99%
“…340 Moreover, crosslinking of siglec-F on mouse eosinophils induced caspase-dependent cell death without ROS production. 340 Ultimately, it was shown that ROS production is essential in the process of EET formation. 146…”
Section: Recep To R Smentioning
confidence: 99%
“…341,342 Furthermore, cross-linking of siglec-8 was reported to induce intracellular ROS production, as well as caspase cleavage and a decrease in mitochondrial membrane potential, resulting in apoptosis in resting human eosinophils. 340 Interestingly, siglec-8 cross-linking on IL-5-primed eosinophils has been shown to induce ROS production along with increased phosphorylation of MEK1 and ERK1/2, leading to caspase-independent necrotic death, while the cross-linking of siglec-8 on IL-33-primed eosinophils resulted in enhanced cell death without ROS production. 340 Moreover, crosslinking of siglec-F on mouse eosinophils induced caspase-dependent cell death without ROS production.…”
Section: Recep To R Smentioning
confidence: 99%
See 1 more Smart Citation